2020
DOI: 10.22175/mmb.10916
|View full text |Cite
|
Sign up to set email alerts
|

Thermophysical Properties of Beef Steaks of Varying Thicknesses Cooked With Low and High Grill Surface Temperatures

Abstract: The objective of this study was to determine the thermodynamic and physical properties of beef strip loin steaks of varying thicknesses and USDA quality grades cooked with high and low grill surface temperatures. Thermal characteristics described by changes in the denaturation temperature (between 55°C – 60°C) and enthalpies of protein denaturation (70°C – 75°C) both differed (P = 0.031 and P = 0.001, respectively) among thick steaks, with thick steaks cooked on a high grill surface temperature having a lower … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 28 publications
2
9
0
Order By: Relevance
“…Therefore, it is safe to conclude that differences in heat transfer among the cooking methods influence the Maillard reaction. Recent work indicates that quality grade or fat content influences thermophysical properties of beef steaks (Gardner et al, 2020). These interactive results may therefore be the result of Standard error (largest) of the least-squares means in the same main effect.…”
Section: Volatile Compound Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is safe to conclude that differences in heat transfer among the cooking methods influence the Maillard reaction. Recent work indicates that quality grade or fat content influences thermophysical properties of beef steaks (Gardner et al, 2020). These interactive results may therefore be the result of Standard error (largest) of the least-squares means in the same main effect.…”
Section: Volatile Compound Analysismentioning
confidence: 99%
“…Heat transfer rates can also be impacted by product composition (Gardner et al, 2020). Differences in quality grades are attributed to differences in intramuscular fat, which can influence the way that steaks conduct heat and therefore impact flavor development (O'Quinn et al, 2012;Legako et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…It is crucial to understand how the thermodynamics of beef can affect palatability. Gardner et al (2020) reported that variations in beef fat composition, thickness, and cooking method impacted the microstructure of beef and overall textural measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Miller et al (2019) have reported the effect of steak thickness, cook surface temperature, and quality grade on consumer and descriptive sensory attributes of the steaks in the current research project reported here. We also investigated the thermophysical properties (Gardner et al, 2020) of steaks from Miller et al (2019) cooked under high and low grill temperatures to determine the physical differences among the treatments. Researchers have reported on cooking temperature effects on palatability (Cross et al, 1976;Knize et al, 1994;Skog et al 1995) but did not include volatile aroma compounds.…”
Section: Introductionmentioning
confidence: 99%